Three-Dimensional Digital Reconstruction of Ti(2)AlC Ceramic Foams Produced by the Gelcast Method - Stiapis, Christos S. (Materials (Basel), 2019)
A digital reconstruction technique is presented that generates three-dimensional (3D) digital representations of ceramic foams created by the foam-gelcasting technique. The reconstruction process uses information that is directly extracted from Scanning Electron Microscopy (SEM) images and offers a 3D representation of the physical sample accounting for the typically large pore cavities and interconnecting windows that are formed during the preparation process. Contrary to typical tessellation-based foam treatments, a spherical representation of the pores and the pore windows of the foams is assumed and a novel hybrid algorithm that combines a variation of Lubachevsky-type and Random Close Packing of Hard Spheres (RCPHS) algorithms has been developed to obtain near-optimum solutions to the packing problem of the spheres that represent the pores. Numerical simulations are performed directly on the 3D reconstructed foams to determine their gas permeability. The model predictions are compared with experimental gas permeability data that were obtained for the physical samples. The pore wall thickness can be treated as the single fitting parameter in the entire reconstruction process, although it is shown that images of sufficient resolution could eliminate the need even for that. The foams that are produced by this method yield quantitatively similar pressure drops with experiments for various superficial velocity values, with a very small deviation in the range of 1.7–2.8%. The proposed methodology could be utilized for the prediction of the permeability and transport properties of complex foamy porous structures, similar to the gelcast-type of foams, from a single SEM image of the foam sample without resorting to serial tomography or other structural information, thus saving considerable time and effort from experimental work.